Interleukin-1 receptor antagonist (anakinra) treatment in patients with systemic-onset juvenile idiopathic arthritis or adult onset Still disease: preliminary experience in France. Issue 3 (18th October 2007) - Lequerré, T; Quartier, P; Rosellini, D; Alaoui, F; De Bandt, M; Mejjad, O; Kone-Paut, I; Michel, M; Dernis, E; Khellaf, M; Limal, N; Job-Deslandre, C; et al.
Abstract : Background: Anakinra treatment has been reported to be effective in some patients with systemic-onset juvenile idiopathic arthritis (SoJIA) or adult-onset Still disease (AoSD). Objectives: To assess the efficacy and the safety of anakinra treatment in SoJIA and AoSD. Methods: SoJIA and AoSD patients were treated with anakinra (1–2 mg/kg/day in children, 100 mg/day in adults); we analysed its effect on fever, erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) levels, numbers of swollen and tender joints, the assessment of disease activity (by physician and parent/patient) and pain (by parent/patient), and American College of Rheumatology (ACR) pediatric core set criteria for JIA activity. Results: A total of 35 patients were included, 20 with SoJIA and 15 with AoSD. Their mean age (range) at the onset of treatment was 12.4 (3–23) and 38.1 (22–62) years, respectively; disease duration was 7.0 (1–16) and 7.8 (2–27) years, respectively. Active arthritis was present in all cases but one. Of the 20 SoJIA patients, 5 achieved ACR 50% improvement in symptoms (ACR50) response criteria at 6 months. Steroid dose had been decreased by 15% to 78% in 10 cases. A total of 11 of the 15 AoSD patients achieved at least a 50% improvement for all disease markers (mean follow-up: 17.5 (11–27) months). Steroids had been stopped in two cases and the dose was decreased by 45% to 95% in 12 patients. Two patients stopped anakinra due to severe skin reaction, and two patients due to infection: one visceral leishmaniasis and one varicella. Conclusion: Anakinra was effective in most AoSD patients, but less than half SoJIA patients achieved a marked and sustained improvement.